The Effect of The Mental Health Literacy Promotion Program on Emotion Regulation Strategies of Family Caregivers of Patients with Chronic Psychiatric Disorders in Isfahan, Iran - Zeynab Pirallahi; Mousa Alavi; Mohammad Akbari; Najme Aliyari (Iranian Journal of Nursing and Midwifery Research, 2025)
Background: Emotion regulation strategies help family caregivers of chronic psychiatric patients to manage caring behaviors. However, evidence pointed out problems and therefore a need to execute respective programs to improve emotion regulation for caregivers. This study aimed to investigate the effectiveness of mental health literacy promotion programs on emotion regulation strategies of family caregivers of chronic psychiatric patients. Materials and Methods: This is a clinical trial study, with two-group pretest–post-test design with a follow-up period conducted in 2023. Sixty family caregivers of chronic psychiatric patients were randomly allocated to intervention control groups. Data collection was done using a demographic characteristics questionnaire and Gross and John’s Emotion Regulation Scale. The mental health literacy promotion program was implemented for the intervention group in six sessions weekly. Immediately and 1 month after the last meeting, the questionnaires were completed. The data were analyzed using Chi-squared and Fisher’s exact tests, Mann–Whitney test, and analysis of covariance by SPSS-22. The significance level was set to 0.05. Results: The results showed that the frequency distribution of demographic variables in the control and test groups had no statistically significant difference (p > 0.05). The intervention had significant effects on the mean score of emotion regulation strategies, and its subscales included re-evaluation and suppression of family caregivers of chronic psychiatric patients in both the post-test and follow-up periods (p < 0.001). Conclusions: According to improving the emotion regulation of family caregivers of chronic psychiatric patients through the mental health literacy promotion program, it is suggested to use this program to achieve the desired emotion regulation.